Using optimization to develop a "designer" environmental flow regime. (February 2017) - Horne, Avril; Kaur, Simranjit; Szemis, Joanna; Costa, Alysson; Webb, J. Angus; Nathan, Rory; Stewardson, Michael; Lowe, Lisa; Boland, Natashia
Abstract: There are increasing numbers of rivers with large storages, resulting in changes to environmental condition downstream. In these systems, environmental flow regimes that are specifically designed to meet environmental management objectives, whilst continuing to support economic needs, may be the best approach. A challenge remains as to how best to design these novel flow regimes. Decision support tools such as optimization provide a potential tool to achieve this. In existing tools environmental outcomes are not represented with sufficient realism and this is a major barrier to successful adoption by decision-makers. Here, we employ conditional probability networks as a promising approach that provides both ease of modelling and a direct link to ecological outcomes and processes. We present a generic model that can be used to represent any ecological endpoint within a river system. We then demonstrate the approach using two fish species in the Yarra River, Victoria.